Penampilan Produksi Sapi Peranakan Ongole dan Sapi Peranakan Ongole x Limousin yang mendapat Pakan Rumput Raja dan Ampas Bir - Edy Rianto; Anna Sofia Iswaldi; Sularno Dartosukarno (Universitas Sebelas Maret, 2005)
An experiment was carried out to compare the performance of Grade Ongole (GO) and its crossing with Limousin (GL) bulls fed King Grass and brewery by-product. Four GO (weighed: 198.50 ± 38.04 kg) and four GL bulls (weighed: 248.84 ± 36,39 kg) were fed king grass and brewery by-product with ratio of 50:50. The amount of dry matter given was 3% of live weight. The parameters measured were feed intake, feed digestibility, liveweight gain (LWG) and feed conversion ratio (FCR). The Results the two breed were not significantly different (P>0.05) in parameters measured. Dry matter intakes of GO and GL were 2,59 and 2.52% of body weight, respectively. The dry matter disgestibilities were 50.98 in GO and 45.74 in GL. Liveweight gains of GO and GL were 0.74 and 0.88 kg/day, respectively. Feed conversion ratios in GO and GL were 8.49, respectively. It was concluded that GO and GL bulls had similar production performance.